الحرب اليابانية الصينية الثانية ۱۹۳۷- 1945 - د. مرتضى عبد الحسين مفتن (Thi Qar Arts Journal, 2021)
The second war china-japan is considered a territorial war; it is a prelude to the second world war which is started in 1939. Waged in 1937, This war is caused by the expansion wave Japan has advocated since the thirties of twentieth century. One front of this expansionism is china. In the military and political history, it is known as mogden war, a chiness city occupied by the japaness forces after the refusal of the chiness government the japaness entrance whose excuse is a search for alost soldier. This is the first spark that Japan has taken as a reason behind occupying the city. Such an invasion, however does not stop the chinese resistance leading the chinese to form what is known as a "united front" a shared force from the china communist party led by mawti tong and the led forces briths, kay tisk, in spit of being smull, the front is able to stop the Japanese invading forces, especially when it come to use a gang war a gainst these forces, finally, the victory was chinese caused by the entrance of japan the second world war against Britain and the united states of America spicily after army Japanese of peril Harber